Developing a training curriculum for researchers working with routine data: understanding professional and lay stakeholder priorities – The CENTRIC Study. (19th November 2019) - Lugg-Widger, Fiona; Munnery, Kim; Townson, Julia; Robling, Mike
No abstract available